Educating about social issues in the 20th and 21st centuries : critical pedagogues and their pedagogical theories - Totten, Samuel; Pedersen, Jon E. (Emerald Publishing Limited : IAP - Information Age Publishing, 2014)
This volume is the fourth, and last, volume in the series entitled Educating About Social Issues in the 20th and 21st Centuries: An Annotated Bibliography. Volumes I and Volume 2 focused on (1) the lives and work of notable scholars dedicated to addressing why and how social issues should become an integral component of the public school curriculum, and (2) various topics/approaches vis--̉vis addressing social issues in the classroom. Volume 3 addressed approaches to incorporating social issues into the extant curricula that were not addressed in the first two volumes. This volume, Volume Four, focuses solely on critical pedagogy: both the lives and work of major critical pedagogues and the different strains of critical pedagogy the latter pursued (e.g., critical theory in education, critical feminism in education, critical race theory).
Keywords: Critical pedagogy.; Educators -- Biography.; Education -- Social aspects.; Education -- Philosophy, Theory & Social Aspects.; Philosophy and theory of education.; elektronické knihy; electronic books